Insights into the global freshwater virome - Elbehery, Ali H. A.; Deng, Li (Frontiers in Microbiology, 2022)
Viruses are by far the most abundant life forms on this planet. Yet, the full viral diversity remains mostly unknown, especially in environments like freshwater. Therefore, we aimed to study freshwater viruses in a global context. To this end, we downloaded 380 publicly available viral metagenomes (>1 TB). More than 60% of these metagenomes were discarded based on their levels of cellular contamination assessed by ribosomal DNA content. For the remaining metagenomes, assembled contigs were decontaminated using two consecutive steps, eventually yielding 273,365 viral contigs longer than 1000 bp. Long enough contigs (≥ 10 kb) were clustered to identify novel genomes/genome fragments. We could recover 549 complete circular and high-quality draft genomes, out of which 10 were recognized as being novel. Functional annotation of these genomes showed that most of the annotated coding sequences are DNA metabolic genes or phage structural genes. On the other hand, taxonomic analysis of viral contigs showed that most of the assigned contigs belonged to the order Caudovirales, particularly the families of Siphoviridae, Myoviridae and Podoviridae. The recovered viral contigs contained several auxiliary metabolic genes belonging to several metabolic pathways, especially carbohydrate and amino acid metabolism in addition to photosynthesis as well as hydrocarbon degradation and antibiotic resistance. Overall, we present here a set of prudently chosen viral contigs, which should not only help better understanding of freshwater viruses but also be a valuable resource for future virome studies.